Os trabalhadores da construção civil, a Escola Zé Peão e as aprendizagens consideradas importantes para o trabalho e para a vida - Oliveira, Ruth Helena Fidelis de Sousa (2015)
The objective of this dissertation is to investigate what worker- s tudents of the Zé Peão School, which is an extra- mural project in Popular Education carried out by the Federal University of Paraiba, consider important to learn for their work and their lives In order to characterize the subjects of the research we had r ecourse to Oliveira (1992) and Souza (2012) and for the analysis of the object we called especially on Frigotto, Ciavatta and Ramos (2014), Oliveira (2006), Araujo (2007) and Pinto (2010). The dialectical historical materialist approach underscored the wri ting of the whole text and our analysis was strongly influenced by the contributions of Löwy (1999), Konder (2008) and Paulo Netto (2011). We discuss the concept of popular education as a humanizing process, proposed by Calado (s/d) and we related it to th e concept of work as an educative principle. Semi- structured interviews making use of focal groups were carried out with six worker- students and an individual interview with one of the pedagogical coordinators of the school who is also financial adviser to the João Pessoa branch of the Building Workers’ Trade Union – SINTRICOM/JP. On the basis of our analysis of the interviews it was possible to observe that the understanding of the learning conceived as necessary for work is strongly influenced by the pers pective of employability and that of competences. However, a second discourse exists which supports the defence of the labour rights of these workers. Some of the learning considered important for life is influenced by demands from the world of work whilst other is based on values with respect to the notion of collectivity.